2011
DOI: 10.1002/dvdy.22614
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of cardiac trabeculation on neuregulin signaling and blood flow in zebrafish

Abstract: COVER PHOTOGRAPH: Three‐dimensional reconstruction of the inner surface of the ventricular chamber of the zebrafish heart. The apparent ridges represent the initial stages of cardiac trabeculation, during which myocardial protrusions transform the previously smooth lumenal surface. From Peshkovsky et al., Developmental Dynamics 240:446‐456, 2011. © 2011 Wiley‐Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Extensive study of intracardiac fluid forces during cardiovascular development has demonstrated important roles in valvulogenesis and trabeculation [1,2,37,38]. Our results suggest that cardiogenesis is also regulated by extracardiac flow forces generated in the pericardial cavity.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Extensive study of intracardiac fluid forces during cardiovascular development has demonstrated important roles in valvulogenesis and trabeculation [1,2,37,38]. Our results suggest that cardiogenesis is also regulated by extracardiac flow forces generated in the pericardial cavity.…”
Section: Discussionmentioning
confidence: 62%
“…As early as the heart tube stage, the heart begins to beat and puts the blood into motion. This generates hemodynamic forces that feed back to the heart, promoting its further maturation through valve formation and myocardial trabeculation [1,2]. At this stage, the myocardium is lined on its lumenal surface by the endocardium, but it is not yet covered by the epicardium, the mesothelial outer layer of the heart.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this idea, neuregulin and notch1b are both expressed in the AV endocardium, and morpholino knockdown of either of these genes inhibits AV delay. Trabecular formation is also dependent on the presence of the endocardium and requires signaling through the neuregulin coreceptor ErbB2 cell-autonomously within the myocardium, demonstrating that some ventricular conduction components rely on the same signals as the AVC myocardium (64,83). Interestingly, different components of the conduction system respond differently to cardiac function.…”
Section: Conduction Systemmentioning
confidence: 95%
“…Also around this time, myocardial sheets known as trabeculae begin to form in the developing ventricle (64,83). In other species, the fast conduction system is thought to form initially within these trabeculae (90,104).…”
Section: Conduction Systemmentioning
confidence: 99%
“…First, cardiomyocytes extend protrusions luminally over their neighbors, and then gradually constrict abluminally while moving their cell body into the trabecular network (Staudt et al, 2014). Neuregulin/ErbB signaling and an optimal blood flow through the ventricle are important for the initiation and advancement of trabeculation (Peshkovsky et al, 2011). This phase is associated with diminished external growth and a switch to internal growth creating numerous trabeculations forming a complex network of lacunae classically referred to as spongy myocardium.…”
Section: Changes In Structure and Anatomymentioning
confidence: 99%